THE IMPACTS OF FIRST LANGUAGE ON STUDENTS’ ENGLISH PRONUNCIATION - Octaviani, Reza Putri; Jannah, Lily Miftahul; Sebrina, Mena; Arochman, Taufik (IJIET (International Journal of Indonesian Education and Teaching), 2024)
This study aims to investigate how and why the first language impacts English Pronunciation Errors. The research design was a case study in the form of qualitative research using contrastive analysis principles to analyze the data. The participants selected were five students from various regions in Indonesia, that was Sunda, Batak, Jakarta, and Java. Each participant in this research studied English as a foreign language in the fourth semester at the Department of English Education at Universitas Tidar. Recorded pronunciation tests and interviews were used to collect data. Online phonetic transcription was used to find errors and transcribe them into phonetic symbols in this study. The finding of this study was the problems of long vowels, consonant sounds, words, and emphasis at the beginning, end, and middle have their respective differences according to their region. Even though the influence of the mother tongue on English pronunciation is quite strong, several methods and techniques can be applied to reduce problems in pronouncing English words.